Reduced bilateral recombination by functional molecular interface engineering for efficient inverted perovskite solar cells. (December 2020) - Li, Bowei; Xiang, Yuren; Jayawardena, K. D. G. Imalka; Luo, Deying; Wang, Zhuo; Yang, Xiaoyu; Watts, John F.; Hinder, Steven; Sajjad, Muhammad T.; Webb, Thomas; Luo, Haitian; Marko, Igor; et al.
Abstract: Interface-mediated recombination losses between perovskite and charge transport layers are one of the main reasons that limit the device performance, in particular for the open-circuit voltage ( V OC ) of perovskite solar cells (PSCs). Here, functional molecular interface engineering (FMIE) is employed to retard the interfacial recombination losses. The FMIE is a facile solution-processed means that introducing functional molecules, the fluorene-based conjugated polyelectrolyte (CPE) and organic halide salt (OHS) on both contacts of the perovskite absorber layer. Through the FMIE, the champion PSCs with an inverted planar heterojunction structure show a remarkable high V OC of 1.18 V whilst maintaining a fill factor (FF) of 0.83, both of which result in improved power conversion efficiencies (PCEs) of 21.33% (with stabilized PCEs of 21.01%). In addition to achieving one of the highest PCEs in the inverted PSCs, the results also highlight the synergistic effect of these two molecules in improving device performance. Therefore, the study provides a straightforward avenue to fabricate highly efficient inverted PSCs. Graphical abstract: Image 1 Highlights: For front-contact modification, the PFN-Br is more beneficial than UV-ozone. For back-contact modification, the PEAI is the best choice amongst organic halide salts.